1987
DOI: 10.1139/f87-078
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Distribution of Phytoplankton in 97 Headwater Lakes in Insular Newfoundland

Abstract: 1987. Factors influencing the distribution of phytoplankton in $7 headwater lakes in insular Newfoundland. Can. ). Fish. Aquat. Sci. 44: 639-649.Phytoplankton samples collected from 97 headwater lakes throughout insular Newfoundland were analyzed and used as a basis for a statistical evaluation of the environmental factors influencing species distributions. A selected subset of 77 taxa were clustered using a complete-linkage cluster analysis. The final 12 clusters represent the associations of species found oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Many authors found a direct relationship between cyanobacterial presence and the mineralization variables (Ca, hardness, etc.) as we have [4]. These results may be explained by the high Ca requirements of many Nz-fixing cyanobacteria [21].…”
Section: Discussionsupporting
confidence: 55%
“…Many authors found a direct relationship between cyanobacterial presence and the mineralization variables (Ca, hardness, etc.) as we have [4]. These results may be explained by the high Ca requirements of many Nz-fixing cyanobacteria [21].…”
Section: Discussionsupporting
confidence: 55%
“…Similar association was documented in a different taxonomic group. Earle et al (1987), for example, reported that clustering groups of 77 phytoplankton taxa collected from 97 headwater lakes in Newfoundland (Canada) were based on specific environmental requirements of species. Our results support their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Except for a few cases, algae were usually identified to species level. A combined minimum of 500 cells, colonies, and filaments were counted per sample as in Earle et al (1987). Counts were expressed as wet biomass (rag/m3).…”
Section: Sampling Protocolmentioning
confidence: 99%